Green growth strategy: The economywide impact of promoting renewable power generation in the Philippines - Pradesha, Angga; Robinson, Sherman; Mondal, Md. Hossain Alam; Valmonte-Santos, Rowena; Rosegrant, Mark W. (International Food Policy Research Institute, 2019)
This study assesses the economywide impact of promoting renewable power generation by targeting a 50 percent share of renewables in energy production by 2040. Using a novel approach by linking a bottom-up energy model with a top-down economywide model, we found that increasing the share of renewables in the power sector could slightly slow down the industrialization process and reduce economic growth. Implementing this policy, however, would allow the country to reduce carbon emissions by 65 million tons in 2040 and improve energy security. The health co-benefit is estimated to reach up to 324 billion Philippine pesos (PHP), which levels the welfare loss. Receiving foreign financial inflow as a compensation for reducing carbon emissions could drive the economy into Dutch disease, shifting more economic activities into the nontradable sector. Increasing total investment demand in the future as a policy response could potentially mitigate this effect and improve economic welfare by 155 billion PHP.